SAN-based composite material with optical waveguide structure and preparation method thereof

By introducing PMMA fiber structure and modified nano CeO2 into the SAN matrix, the problem of insufficient transmittance of SAN material in the ultraviolet band was solved, realizing deep UV adhesive curing of electrophoretic plates and high-performance application of materials.

CN121249064APending Publication Date: 2026-01-02中广核俊尔(浙江)新材料有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511629864.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-08
Publication Date
2026-01-02

AI Technical Summary

Technical Problem

The insufficient light transmittance of SAN material in the 300-350nm wavelength range prevents low-concentration UV adhesive from effectively penetrating the electrophoresis plate, resulting in delamination curing and affecting the function of the electrophoresis plate.

Method used

By introducing high-flowability PMMA resin into the SAN matrix to form an axially continuous fiber structure, total internal reflection is achieved by utilizing the refractive index difference between PMMA and SAN. Combined with the Rayleigh scattering effect of modified nano CeO2, maleic anhydride-grafted SEBS is used as a compatibilizer to construct chemical bonds at the interface. The optical waveguide structure is prepared by combining slit die extrusion, longitudinal hot stretching and water bath quenching process.

Benefits of technology

It significantly improves the transmittance of SAN-based composite materials in the 300-350nm wavelength range to over 80%, ensuring deep and uniform curing of low-concentration UV adhesives. The material has high UV transmittance, excellent mechanical properties, and good chemical resistance, making it suitable for microfluidic chips, electrophoresis plates, and optoelectronic devices.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an optical waveguide structure composite material based on SAN resin and a preparation method thereof. The raw material composition is as follows: 60-70 parts of SAN resin; 30 to 40 parts of PMMA (polymethyl methacrylate) resin; 0.1 to 1 part of modified nano CeO2; 1 to 5 parts of a maleic anhydride grafted SEBS compatilizer; and 0.1 to 1 part of an antioxidant. According to the material, through a double-effect anti-reflection mechanism of a synergistic effect, the light transmittance gt of a key ultraviolet band is remarkably improved; on one hand, the refractive index difference between the PMMA fibers which are continuously distributed in the axial direction and the SAN matrix is utilized to guide ultraviolet light to generate total internal reflection conduction at an interface, and the inherent strong ultraviolet absorption characteristic of the SAN matrix is effectively avoided; on the other hand, by means of the Rayleigh scattering effect generated by the CeO2 nanoparticles which are subjected to double surface modification and are uniformly dispersed, the transmission efficiency of ultraviolet light is selectively enhanced. According to the preparation method, a slit die head is adopted for extrusion preforming, and key processes of longitudinal hot stretching (inducing PMMA fibrosis) and water bath shock cooling (locking an optical waveguide microstructure) are combined, so that precise construction and large-scale preparation of an optical waveguide structure in the material are realized. The prepared composite material has high ultraviolet light transmittance, excellent mechanical properties and good chemical resistance, and has wide application prospects in the fields of micro-fluidic chips, electrophoresis plates, medical instruments and optoelectronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to polymer composite material technology, specifically to a SAN-based composite material with an optical waveguide structure and its preparation method. Background Technology

[0002] As a core functional component of the electrophoresis tank, the choice of material for the electrophoresis plate directly affects the equipment's performance and reliability. Early materials commonly used glass, but its inherent brittleness and high density made it prone to damage during transportation and use. To meet the demands for lightweighting and portability, engineering plastics such as polymethyl methacrylate (PMMA) and polycarbonate (PC) were introduced. However, PMMA suffers from insufficient resistance to organic solvents and is prone to swelling and deformation; while PC offers good overall performance, its high cost limits large-scale industrial application.

[0003] SAN materials, with their excellent rigidity, outstanding chemical corrosion resistance, good injection molding processability, and significant cost advantages, have become ideal candidates to replace the aforementioned materials. However, the benzene ring structure in the SAN molecular chain has strong absorption characteristics for ultraviolet light, especially in the 300-350nm band (the key activation wavelength for curing low-concentration UV adhesives), resulting in severely insufficient light transmittance in this band.

[0004] This defect is particularly prominent in electrophoresis processes using low-concentration UV adhesives: low-concentration UV adhesives have low photoinitiation efficiency and are extremely sensitive to the transmittance of the substrate. When the transmittance of the substrate in the 300-350nm wavelength range is below 80%, the incident UV light intensity is insufficient to penetrate the material and induce deep curing, resulting in delamination curing of the adhesive (the surface layer is cured while the bottom remains sticky), causing the electrophoresis plate to malfunction. Therefore, overcoming the transmittance limitation of SAN materials in the critical ultraviolet band (300-350nm) is a core technological bottleneck that must be addressed for its application in high-performance electrophoresis plates. Summary of the Invention

[0005] To address the shortcomings in this field, the present invention provides a SAN-based composite material with an optical waveguide structure and its preparation method. The composite material uses SAN resin as a continuous phase matrix and achieves a significant increase in ultraviolet transmittance through a ternary synergistic mechanism: under specific processing conditions, high-flowability PMMA resin is introduced, forming an axially continuous fiber structure within the SAN matrix. Utilizing the refractive index difference between PMMA and SAN, incident ultraviolet light undergoes total internal reflection at the PMMA / SAN interface, enabling long-distance transmission within the PMMA fibers and effectively avoiding the strong absorption of ultraviolet light by the SAN matrix. Nano-CeO2, modified with both a silane coupling agent and zinc stearate, is introduced. Its nanoscale uniform dispersion selectively enhances the light transmission efficiency in the ultraviolet band (300-400 nm) through Rayleigh scattering. Maleic anhydride-grafted SEBS is used as a compatibilizer. Its anhydride groups form chemical bonds with the cyano groups of SAN and the carbonyl groups of PMMA, and a trace amount of crosslinking agent initiates mild crosslinking, constructing a stable structure with synergistic chemical and physical reinforcement at the interface, ensuring the integrity of the optical waveguide fiber during processing and use. The core of the preparation method lies in: achieving melt pre-shaping through slit die extrusion, combined with precisely controlled longitudinal thermal stretching (inducing continuous fiberization of the PMMA phase) and low-temperature water bath quenching (rapidly freezing the microstructure), enabling controllable preparation and mass production of the optical waveguide structure. Ultimately, this composite material achieves a transmittance ≥80% in the key ultraviolet band (300-350nm), effectively solving the problem of deep and uniform curing of low-concentration UV adhesives.

[0006] A SAN-based composite material with an optical waveguide structure and its preparation method, comprising the following raw materials in parts by mass: SAN resin: 60-70 parts PMMA resin: 30-40 parts Modified nano CeO2: 0.1-1 parts Maleic anhydride grafted with SEBS compatibilizer: 1-5 parts Antioxidant: 0.1-1 part.

[0007] The composite material is in granular form, and the PMMA phase inside the granules exhibits an axial fiber structure.

[0008] The PMMA resin is in granular form, and the melt flow index measured at 230℃ and 3.8kg is 15-30g / 10min.

[0009] The modified nano CeO2 undergoes dual surface treatment with silane coupling agent and zinc stearate, while other stearates have little or no effect on light transmittance.

[0010] The silane coupling agents are one or more combinations of KH550, KH560, KH570, KH580, and KH590.

[0011] The maleic anhydride-grafted SEBS compatibilizer contains 0.2%-0.4% by mass of a crosslinking agent; wherein the crosslinking agent is preferably one or more of DCP, DTBP, DBHP, and TAIC; the compatibilizer containing a crosslinking agent means that the crosslinking agent is first made into a masterbatch with the compatibilizer as the base material.

[0012] The antioxidant is one or more of 1010, 1076 and 168.

[0013] The preparation method of the SAN-based composite material with optical waveguide structure includes the following steps: First, SAN resin, PMMA resin and maleic anhydride-grafted SEBS compatibilizer are premixed, and then the premix is ​​added to the main feed port of a twin-screw extruder; modified nano-CeO2 is added from the side feed port of the sixth section of the twin-screw extruder; the melt after melt blending is extruded through a slit die, and then longitudinally stretched in a hot air zone of about 120°C to 2-3 times the original length; the stretched melt is subjected to rapid cooling and solidification in a water bath at about 5-10°C, and the solidified material is subjected to underwater pelletizing. The resulting pellets are dried at 85°C for about 4 hours to finally obtain the SAN-based composite material with optical waveguide structure.

[0014] The temperature zones of the twin-screw extruder are set as follows: feeding zone 185-195℃, melting zone 210-220℃, homogenization zone 200-210℃, and screw speed controlled at 250-400 r / min.

[0015] The slit die head has a built-in rectifier with a honeycomb flow channel, the flow channel diameter being 5-8 times the target diameter of the PMMA axial fibers in the final composite material.

[0016] The prepared composite material has high ultraviolet transmittance, excellent mechanical properties and good chemical resistance, showing broad application prospects in the fields of microfluidic chips, electrophoresis plates, medical devices and optoelectronic devices.

[0017] Compared with the prior art, the present invention has the following advantages: 1. Breakthrough Improvement in Transmittance of Key Ultraviolet Bands: Through the synergistic enhancement mechanism of "PMMA fiber total internal reflection waveguide" and "modified nano-CeO2 Rayleigh scattering enhancement," this invention successfully increases the transmittance of SAN-based composite materials in the key ultraviolet band of 300-350nm to over 80%. This fundamentally overcomes the transmittance bottleneck of SAN materials caused by the strong ultraviolet absorption of the benzene ring structure, providing reliable light transmission assurance for the deep and uniform curing of low-concentration UV adhesives in electrophoresis plates, and solving the core obstacle to its application.

[0018] 2. Controllable Fabrication and Mass Production of Optical Waveguide Structures: This invention develops a core process combination based on slit die extrusion pre-shaping, longitudinal thermal stretching-induced fiberization, and water bath quenching to lock the microstructure. This process system achieves precise and stable construction of axially continuous, high aspect ratio PMMA fiber structures within the composite material. Its process parameters (temperature, stretch ratio, cooling rate) are highly controllable, exhibiting excellent repeatability and industrial adaptability, and can meet the needs of large-scale continuous production of high-performance electrophoretic coating materials.

[0019] 3. Excellent overall performance and cost-effectiveness: Using SAN resin, which has a significant cost advantage, as the continuous phase matrix, high UV transmittance is achieved while retaining the inherent high rigidity, excellent chemical resistance, and good injection molding processability of SAN materials. Compared with PC-based electrophoresis plate materials, the material cost is significantly reduced, providing an electrophoresis plate solution that combines high performance and cost-effectiveness, better meeting the actual needs of large-scale industrial applications. Implementation

[0020] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Operating methods not specifically specified in the following embodiments are generally performed under conventional conditions or as recommended by the manufacturer.

[0021] The raw material composition of each embodiment is shown in Table 1 by mass parts. Among them, high-flow PMMA with a melt index (230℃, 3.8kg) of 20g / min is used; modified nano CeO2 with an average particle size of 50±20nm is treated with silane coupling agent KH560 and zinc stearate for double surface treatment.

[0022] The preparation method of the example is as follows: According to the proportions in Table 1, SAN resin, PMMA resin, maleic anhydride-grafted SEBS compatibilizer, and antioxidant were added to a high-speed mixer and mixed evenly. The mixture was then fed into the main feed port of a twin-screw extruder. Modified nano-CeO2 was added through the side feed port of the sixth section of the barrel. The extrusion temperature was 190-210℃, and the screw speed was 350 r / min. After the melt was extruded through a slit die, it entered a 120℃ hot air zone for longitudinal stretching (stretch ratio of 2), and then rapidly cooled and shaped in a 10℃ water bath. The product was then underwater pelletized and dried at 85℃ for 4 hours to obtain SAN-based composite material particles with an optical waveguide structure.

[0023] Components / Specifications Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Example 1 Example 2 Example 3 SAN resin 65 65 65 65 65 65 60 70 PMMA resin 35 35 35 35 35 35 40 30 <![CDATA[Modified nano - CeO2]]> - 0.5 0.5 - - 0.5 0.1 1.0 <![CDATA[Ordinary CeO2]]> - - - 0.5 - - - - <![CDATA[Modified nano - CeO2 (double surface treatment with silane coupling agent KH560 and calcium stearate)]]> - - - - 0.5 - - - Maleic anhydride grafted with SEBS compatibilizer - 3 (including 0.3% DCP) - 3 (including 0.3% DCP) 3 (including 0.3% DCP) 3 (including 0.3% DCP) 5 (includes 0.4% TAIC) 1 (containing 0.2% DBHP) antioxidants 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Key processes No stretching / rapid cooling No stretching / rapid cooling Same as the embodiment Same as the embodiment Same as the embodiment According to the instructions According to the instructions According to the instructions The raw material composition and proportions of Comparative Examples 1-5 are also as shown in Table 1. The main differences between their preparation methods and those of the Examples are as follows: Comparative Examples 1 and 2 did not undergo longitudinal stretching and rapid cooling shaping processes after melt extrusion.

[0024] The SAN-based composite material particles were injection molded into 1 mm thick samples. The ultraviolet transmittance of the samples at 365 nm wavelength was tested according to GB / T 2410 standard. The diameter and morphology of the PMMA fibers were observed using an optical microscope. A UV adhesive layer of approximately 3 mm was coated onto the samples, and the curing effect was evaluated using the finger-pressing method. The changes in characteristic functional groups before and after curing were tracked using Fourier transform infrared spectroscopy to quantitatively analyze the degree of curing. The SAN-based composite material particles were injection molded into standard mechanical test strips. Tensile strength was tested according to GB / T 1040.2, flexural strength according to GB / T 9341, and notched impact strength of simply supported beams according to GB / T 1043.2.

[0025] Components / Specifications Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Example 1 Example 2 Example 3 Ultraviolet transmittance (365nm) (%) 45 48 69 65 71 86 83 82 Fiber diameter (μm) / / / / / 20 18 25 3mm UV adhesive curing effect Sticky bottom Sticky bottom Localized uncured Localized uncured vitiligo Localized uncured vitiligo Fully cured Fully cured Fully cured Tensile strength (MPa) 45 50 55 52 62 62 60 68 Bending strength (MPa) 70 75 80 78 86 85 82 88 <![CDATA[Notched impact strength of simply supported beam (kJ / m 2 )]]> 1.5 2.0 1.3 1.7 2.4 2.3 2.7 2.0 As shown in Table 2, Comparative Example 1 (traditional blend) lacks a directional flow field, resulting in Mie scattering due to the island-like dispersion of PMMA. The transmittance at 365nm is only 45%, and the weakened interface leads to an impact strength of 1.5kJ / m². The UV adhesive underlayer is sticky, proving that SAN UV absorption was not avoided. Comparative Example 2 also did not use the stretching / quenching core process and lacks an optical waveguide structure, resulting in a transmittance of only 48%. This confirms the necessity of the stretching flow field and quenching process for constructing the total internal reflection channel. Comparative Example 3, without the addition of maleic anhydride-grafted SEBS compatibilizer, showed interfacial instability and PMMA fiber breakage, with impact strength decreasing to 1.3 kJ / m², confirming the indispensable synergistic strengthening mechanism of interfacial chemical bonding and cross-linking network; Comparative Example 4, using unmodified CeO2, showed Mie scattering (white spots) induced by particle aggregation, with a transmittance of 65%, highlighting the decisive role of dual surface treatment in enhancing nano-dispersion and Rayleigh scattering; Comparative Example 5, with CeO2 treated with silane coupling agent KH560 and calcium stearate, showed little change in UV transmittance.

[0026] Example 1: After stretching at 120°C and quenching in a 10°C water bath, axially continuous PMMA fibers with a diameter of approximately 20 μm and an aspect ratio >150 were formed. Synergistic modification of CeO2 with uniform dispersion and maleic anhydride-grafted SEBS compatibilizer enhanced the interface, achieving a light transmittance of 86% at 365 nm and an impact strength of 2.3 kJ / m². Example 2: With PMMA increased to 40 parts and fibers refined to 18 μm, the increased total interface area resulted in a slight decrease in light transmittance to 83%. However, the TAIC crosslinking agent, in conjunction with the maleic anhydride-grafted SEBS compatibilizer, constructed a three-dimensional network, increasing the impact strength to 2.7 kJ / m². Example 3: With SAN increased to 70 parts, the matrix rigidity was improved, resulting in coarser fibers. The tensile strength increased to 68 MPa, but insufficient maleic anhydride-grafted SEBS compatibilizer led to insufficient interface strengthening, causing the impact strength to decrease to 2.0 kJ / m², confirming that the compatibilizer dosage must match the interface area.

[0027] This invention provides a SAN resin-based optical waveguide composite material and its preparation method. The material significantly improves the transmittance (>80%) in the key ultraviolet band through a synergistic dual-effect anti-reflection mechanism: on the one hand, by utilizing the refractive index difference between the axially continuously distributed PMMA fibers and the SAN matrix, ultraviolet light is guided to undergo total internal reflection at the interface, effectively avoiding the inherent strong ultraviolet absorption characteristics of the SAN matrix; on the other hand, by leveraging the Rayleigh scattering effect generated by the double-surface-modified, uniformly dispersed CeO2 nanoparticles, the transmission efficiency of ultraviolet light is selectively enhanced. The preparation method employs slit die extrusion preforming, combined with key processes of longitudinal thermal stretching (inducing PMMA fiberization) and water bath quenching (locking the optical waveguide microstructure), achieving precise construction and large-scale fabrication of the internal optical waveguide structure. The prepared composite material possesses high ultraviolet transmittance, excellent mechanical properties, and good chemical resistance, showing broad application prospects in medical devices such as microfluidic chips and electrophoresis plates, as well as optoelectronic devices.

[0028] Furthermore, it should be understood that after reading the above description of the present invention, those skilled in the art can make various alterations and modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims.

Claims

1. A SAN-based composite material with an optical waveguide structure, comprising, by weight, the following raw materials: SAN resin: 60-70 parts PMMA resin: 30-40 parts Modified nano CeO2: 0.1-1 parts Maleic anhydride grafted with SEBS compatibilizer: 1-5 parts Antioxidant: 0.1-1 part; The composite material is in granular form, and the PMMA phase inside the granules exhibits an axial fiber structure. The modified nano CeO2 undergoes a dual surface treatment with a silane coupling agent and zinc stearate.

2. The SAN-based composite material with an optical waveguide structure according to claim 1, characterized in that, The PMMA resin is in granular form, and the melt flow index measured at 230℃ and 3.8kg is 15-30g / 10min.

3. The SAN-based composite material with an optical waveguide structure according to claim 1, characterized in that, The silane coupling agents are one or more combinations of KH550, KH560, KH570, KH580, and KH590.

4. The SAN-based composite material with an optical waveguide structure according to claim 1, characterized in that, The maleic anhydride-grafted SEBS compatibilizer contains 0.2%-0.4% by mass of a crosslinking agent.

5. A SAN-based composite material with an optical waveguide structure according to claim 4, characterized in that, The crosslinking agent is one or more of DCP, DTBP, DBHP, and TAIC.

6. A SAN-based composite material with an optical waveguide structure according to claim 1, characterized in that, The antioxidant is one or more of 1010, 1076 and 168.

7. A method for preparing a SAN-based composite material with an optical waveguide structure according to any one of claims 1-7, characterized in that, Specifically, the following steps are included: First, SAN resin, PMMA resin, and maleic anhydride-grafted SEBS compatibilizer are premixed. Then, the premix is ​​added to the main feed port of a twin-screw extruder. Modified nano-CeO2 is added from the side feed port of the sixth barrel of the twin-screw extruder. The melt after melt blending is extruded through a slit die and then longitudinally stretched in a hot air zone at about 120°C to 2-3 times its original length. The stretched melt is then subjected to rapid cooling and solidification in a water bath at about 5-10°C. The solidified material is then subjected to underwater pelletizing, and the resulting pellets are dried at 85°C for about 4 hours to finally obtain a SAN-based composite material with an optical waveguide structure.

8. A method for preparing a SAN-based composite material with an optical waveguide structure as described in claim 8, characterized in that, The temperature zones of the twin-screw extruder are set as follows: feeding zone 185-195℃, melting zone 210-220℃, homogenization zone 200-210℃, and screw speed controlled at 250-400 r / min.

9. A method for preparing a SAN-based composite material with an optical waveguide structure as described in claim 8, characterized in that, The slit die head has a built-in rectifier with a honeycomb flow channel, the flow channel diameter being 5-8 times the target diameter of the PMMA axial fibers in the final composite material.

10. The SAN-based composite material with an optical waveguide structure according to claim 1 is applied to the fields of microfluidic chips, electrophoresis plates, medical devices and optoelectronic devices.